Rational design of potent ultrashort antimicrobial peptides with programmable assembly into nanostructured hydrogels - Cardoso, Priscila; Appiah Danso, Samuel; Hung, Andrew; Dekiwadia, Chaitali; Pradhan, Nimish; Strachan, Jamie; McDonald, Brody; Firipis, Kate; White, Jacinta F.; Aburto-Medina, Arturo; Conn, Charlotte E.; Valéry, Céline (Frontiers in Chemistry, 2023)
Microbial resistance to common antibiotics is threatening to cause the next pandemic crisis. In this context, antimicrobial peptides (AMPs) are receiving increased attention as an alternative approach to the traditional small molecule antibiotics. Here, we report the bi-functional rational design of Fmoc-peptides as both antimicrobial and hydrogelator substances. The tetrapeptide Fmoc-WWRR-NH2—termed Priscilicidin—was rationally designed for antimicrobial activity and molecular self-assembly into nanostructured hydrogels. Molecular dynamics simulations predicted Priscilicidin to assemble in water into small oligomers and nanofibrils, through a balance of aromatic stacking, amphiphilicity and electrostatic repulsion. Antimicrobial activity prediction databases supported a strong antimicrobial motif via sequence analogy. Experimentally, this ultrashort sequence showed a remarkable hydrogel forming capacity, combined to a potent antibacterial and antifungal activity, including against multidrug resistant strains. Using a set of biophysical and microbiology techniques, the peptide was shown to self-assemble into viscoelastic hydrogels, as a result of assembly into nanostructured hexagonal mesophases. To further test the molecular design approach, the Priscilicidin sequence was modified to include a proline turn—Fmoc-WPWRR-NH2, termed P-Priscilicidin–expected to disrupt the supramolecular assembly into nanofibrils, while predicted to retain antimicrobial activity. Experiments showed P-Priscilicidin self-assembly to be effectively hindered by the presence of a proline turn, resulting in liquid samples of low viscosity. However, assembly into small oligomers and nanofibril precursors were evidenced. Our results augur well for fast, adaptable, and cost-efficient antimicrobial peptide design with programmable physicochemical properties.